Organoleptic Test of Fruit Leather Made from Dragon Fruit Peel - Deswinta, Tonny; Dalem, A.A. GD. Putra K.P.; Pujawan, Anak Agung Ketut Alit (PT FORMOSA CENDEKIA GLOBAL, 2024)
Fruit leather is a food product in the form of dried sheets of fruit pulp that tastes sweet and has a soft rubber-like texture, which is processed by rehydrating fruit puree. Because the skin of the dragon fruit is only thrown away and becomes a waste, alternative processing is needed to utilize the skin of the dragon fruit. The method used in this study is descriptive qualitative which aims to determine and describe the organoleptic quality of Fruit leather by using dragon fruit skin which is reviewed from the taste, aroma, texture and color. The results of the research Fruit leather dragon fruit skin in terms of taste obtained an index value of 86%, in terms of aroma obtained an index value of 81%, in terms of texture obtained an index value of 85%, in terms of color obtained 86%, with an average total of 84.5%.